An Outline of Integrating Vision Screening at a Student-Run Free Health Clinic - Carol Beatty; Brittany Sheffield; Taryn Lykes; Grace Greenway; Hannah E Myers (Journal of Student-Run Clinics, 2024)
Visual impairment (VI) is a pervasive issue associated with a significant financial burden, diminished health outcomes, and an overall reduced quality of life. This condition disproportionately affects uninsured patients as they face limited access to affordable care. For this reason, FaithCare Clinic, a free, student-run clinic in Augusta, Georgia that serves uninsured and underinsured patients at least two standard deviations below the poverty line, implemented a vision screening and referral protocol to better serve its patients. Patients were approached after check-in for their appointment, but prior to seeing the physician, and were screened with a Snellen Eye Chart and Amsler Grid to assess for refractive error and other types of VI. If they screened positive, they were referred to low cost, local resources for further care. Data was collected over a period of 17 months with 47.8% of the patients seen in clinic offered vision screening. Of the patients offered screening, the majority accepted (79.1%). Half of patients screened were cleared while the other half were referred for further care. These results illustrate that patients of a free clinic are willing to undergo vision screening and can benefit from its offering due to the high rates of VI in this population. Visual disabilities are a heavy burden, especially on the uninsured and underinsured populations. Implementing vision screening in free clinics across the country can identify and facilitate additional care in an at-risk population with minimal training and few additional resources.